The anatomy of dance discourse : literary and philosophical approaches to dance in the later Graeco-Roman world - Schlapbach, Karin (Oxford University Press, 2018)
This work offers a fresh, original perspective on ancient perceptions of dance. Focusing on the second century CE, it provides an overview of the dance discourse of this period, juxtaposing philosophical and literary conceptualizations of dance and exploring how they interacted with different areas of cultural expression